The Influence of Motivation and Work Stress on the Performance of Nurses - Sitanggang, Verayanty; Lubis, Arlina Nurbaity; Sudaryati, Etti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nurses have a professional obligation to care for patients in various conditions, including during the COVID-19 pandemic. Carrying out health services in hospitals is very necessary to achieve optimal performance. This study aims to analyze the influence of work motivation and work stress on the performance of nurses in Medan City Hospital type B. The study was cross-sectional. 133 nurses were involved using total sampling. Data were collected using the work motivation questionnaire. Data were analyzed using the Pearson relation test and the multiple linear regression. The results show that there is an influence of work motivation on the performance of executive nurses at Medan City Hospital (α=0.035, p-value <0.05) and there is an influence of work stress on the performance of executive nurses at Medan City Hospital (α=0.040, p-value <0.05). The research results based on the results of multiple regression tests show that there is a significant influence between work motivation and work stress on the performance of implementing nurses in Medan City private hospitals (α=0.000).